Implikasi Hukum Perdata dalam Kontrak Bisnis: Tinjauan terhadap Keabsahan dan Pelaksanaannya di Indonesia - Pribadi, Adhimaz Kondang (Muhammadiyah Law Review Journal, 2025)
Business contracts are a crucial element in the economic activities of Indonesia; however, the existing contract law is still grounded in classical principles that do not fully accommodate the dynamics of modern business. This study employs a normative legal approach, utilizing legislative, conceptual, and case study methodologies. Data were collected through literature reviews, interviews with legal practitioners, and analyses of court rulings related to business contract disputes. The findings indicate that legal certainty in the enforcement of business contracts in Indonesia remains low, characterized by slow and inefficient enforcement processes. Issues of contract validity, particularly concerning language use and unfair clauses, frequently lead to legal uncertainty. Furthermore, advancements in technology and globalization necessitate a more responsive legal adaptation, including the recognition of electronic contracts